2005
DOI: 10.1161/01.atv.0000163840.63685.0c
|View full text |Cite
|
Sign up to set email alerts
|

Statins Reduce Interleukin-6–Induced C-Reactive Protein in Human Hepatocytes

Abstract: Objectives-Besides its predictive role in determining cardiovascular risk, C-reactive protein (CRP) may exert direct proatherogenic effects through proinflammatory properties. CRP is mainly produced by hepatocytes in response to interleukin-6 (IL-6) and is then released into the systemic circulation. 3-hydroxy-3-methylglutaryl (HMG)-coenzyme A (CoA) reductase inhibitors, or statins, significantly reduce cardiovascular events and mortality in patients with or without coronary artery disease and reduce plasma CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(141 citation statements)
references
References 67 publications
4
132
0
5
Order By: Relevance
“…Of note activation of STAT3 is important for the protective effects of HO-1 and CO against hyperoxia-induced murine lung injury (42). However, whereas STAT3 merits further investigation as a downstream mediator of LSS ϩ atorvastatin-induced HO-1, it has been reported that both statins (43,44) and shear stress (45) may inhibit STAT3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note activation of STAT3 is important for the protective effects of HO-1 and CO against hyperoxia-induced murine lung injury (42). However, whereas STAT3 merits further investigation as a downstream mediator of LSS ϩ atorvastatin-induced HO-1, it has been reported that both statins (43,44) and shear stress (45) may inhibit STAT3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…In single studies, statin-induced lowering of LDL-C and reductions in hsCRP correlate weakly [100], though a recent meta-analysis of LDL-C lowering intervention trials showed a strong correlation between LDL-C and hsCRP [101]. This suggests that different individuals may vary in achieving the amount of LDL-C lowering required to reduce inflammatory responses reflected by hsCRP [102].…”
Section: Stimuli Triggering Crpmentioning
confidence: 99%
“…Although the clinical trial evidence strongly supports that the vast majority of benefit with the use of lipid-altering drugs relates to the alteration of lipids, potential nonlipid antiinflammatory effects on hsCRP levels cannot be ruled out [102]. It also cannot be discounted that hsCRP may potentially have some direct role in the pathogenesis of atherosclerosis, such as enhancing the uptake of oxidized LDL by endothelial cells and macrophages, decreasing nitric oxide production and inducing the expression of vascular cell adhesion molecules [95].…”
Section: Stimuli Triggering Crpmentioning
confidence: 99%
“…Statins reduce CRP production in response to stimuli such as IL-6 in vitro (165) and reduce CRP levels in vivo, correlating with low-density lipoprotein-independent improvement in cardiovascular outcome (163,166,167). Whether CRP is itself pathogenic in atherosclerosis, or whether elevated CRP levels merely reflect the presence of inflammatory mediators such as IL-6, remains to be determined (168,169).…”
Section: Statin Trials In Human Inflammatory and Autoimmune Diseasesmentioning
confidence: 99%